Combate à “heresia espírita”: os enfrentamentos entre espiritismo e catolicismo no campo religioso (Rio Grande do Sul, 1953-1965) - Scherer, Bruno Cortês (2020)
This work deals with the clashes between Catholicism and Spiritism in Rio Grande do Sul, focusing on the development of the National Campaign Against Spiritist Heresy, between the years 1953 and 1965. Adopting periodicals produced by its representative bodies as the main sources of analysis, it identifies and reflects on the strategies, speeches and actions of Catholic and Spiritist agents, questioning their impact on the configuration of the religious field in the middle of the 20th century. The study points to an intense religious competition, with the anti-spiritual campaign being erected in the face of the growth and influence of spiritism in Brazilian society. In a confrontation that crossed the limits of the religious scope, spiritism actively responded to the oppositions that were addressed to it using its organizational structure, the periodical press and a cohesive project of intervention in the social space. Those elements that, to a certain extent, allowed it to mitigate the effects of the Catholic struggle and to guarantee its position in the religious field and in the society of Rio Grande do Sul. The study is part of the line of research called Culture, Migration and Work, of the History Postgraduate Program at the Federal University of Santa Maria, Doctorate level, with a concentration area of History, Power and Culture.